Xerostomia severity difference between elderly using alcohol and non-alcohol containing mouthwash - Hendri Susanto (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: There are alcohol and non alcohol-containing mouthwash available in the market. Alcohol-containing mouthwash may have side effects which induced by alcohol in the mouthwash. Dry mouth/xerostomia may be a potential side effect of alcoholcontaining mouthwash when used by elderly person who has a tendency to have dry mouth. The evidence of  xerostomia induced by alcohol-containing mouthwash used by elderly is not available yet. Purpose: The aim of this study is to know the differences of xerostomia severity between elderly use alcohol-containing mouthwash and non alcohol-containing mouthwash. Method: This study was performed in elderly with age above sixty who do not have systemic diseases based on anamnesis, do not have oral diseases, and do not have allergy to one of  mouthwash components, do not use denture. Of total, thirty elderly participated in this study. The first group consists of elderly who use alcohol-containing mouthwash (AM) and the second group consists of elderly who use non alcoholcontaining mouthwash (NAM). Both groups use mouthwash for seven days (one week) twice a day. Xerostomia severity was assessed by VAS questionnaire. The mean score of the visual analogue score (VAS) xerostomia each group in day one (baseline) and day eight (post treatment) was analyzed by the Wilcoxon sign ranked test and Mann Whitney U test with 95% confidence level. Result: The VAS score of xerostomia post treatment (mean+SD/19.47+8.33) higher than baseline (mean+SD/15.87+8.91) in AM group (p<0.05), but, there is no significant difference of VAS score of xersotomia between post treatment (mean+SD/23.53+10.81) and baseline (mean+SD/23.67+11.82) in NAM group (p>0.05). The mean difference of VAS score of post-treatment and baseline between AM and NAM group was not significant (p>0.05). Conclusion: The conclusion is no significance difference of xerostomia severity between alcohol-containing mouthwash and non alcohol-containing mouthwash in elderly.